2012
DOI: 10.1039/c2cp40680b
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β fibril disruption by C60—molecular guidance for rational drug design

Abstract: The WHO has listed Alzheimer's disease among the major neurological disorders with an estimated 35 million people affected worldwide. Amyloid-β is mostly believed to be the causative factor in Alzheimer's disease and the severity of the disease correlates with the tendency of amyloid-β to form aggregation patterns-plaques. Lacking effective medication, the identification of any underlying mechanistic principles regarding plaque formation appears to be crucial. Here we carry out computer simulations to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 35 publications
12
98
0
Order By: Relevance
“…The results show that the presence of C60 inhibits the formation of the characteristic fibril favoring β-hairpin as well as the extended conformation suggesting that the interactions with the C60 may contribute to an increase in mobility (see Figure S1) and facilitate the formation of fibril incompetent conformations. Recent work by Andujar et al where they showed that C60 induced significant destabilization of the amyloid-β fibrils by disrupting the hydrophobic contacts and salt-bridges between the β-sheets [76] is in line with our work. This suggests that C60 can be used as a prototype for the design of potential fibril inhibitors.…”
Section: Resultssupporting
confidence: 93%
“…The results show that the presence of C60 inhibits the formation of the characteristic fibril favoring β-hairpin as well as the extended conformation suggesting that the interactions with the C60 may contribute to an increase in mobility (see Figure S1) and facilitate the formation of fibril incompetent conformations. Recent work by Andujar et al where they showed that C60 induced significant destabilization of the amyloid-β fibrils by disrupting the hydrophobic contacts and salt-bridges between the β-sheets [76] is in line with our work. This suggests that C60 can be used as a prototype for the design of potential fibril inhibitors.…”
Section: Resultssupporting
confidence: 93%
“…Small natural molecules, vitamin analogues, drugs like naproxen, ibuprofen were studied against AD and for their inhibitory mechanism (Lemkul et al, 2010;Takeda et al, 2010;Choi et al, 2008;Andujar et al, 2012;Huy et al, 2013;Richard et al, 2013 ). However, the interaction of various destabilizing agents with amyloid oligomer and their mechanism is still largely unknown (Lemkul et al, 2010;Takeda et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…23,24 However, structural information on the monomeric and various self-assembled forms has been obtained via NMR methods. [35][36][37][38][39] Kim and Lee rst showed that 1,2-(dimethoxylmethano) fullerene specically binds to the KLVFF region of the Ab protein, thereby suppressing Ab aggregation. 7,18,[26][27][28][29][30] Non-covalent interactions arising from various nanomaterials could be harnessed for modulating the intrinsic selfassembly characteristics of Ab.…”
Section: Introductionmentioning
confidence: 99%